WORKPLACE LEARNING IN THE CONTEMPORARY SUPERVISION LANDSCAPE: THE CASE OF SUPERVISION IN A SOCIAL SERVICE ORGANISATION - Sithole, Mbongeni Shadrack; Shokane, Allucia Lulu (Social Work, 2023)
The blurring of the boundaries and interconnectedness between learning and work are features worth exploring in the contemporary supervision landscape. Grounded on transition-experiential learning theories, the study analysed a social service organisation as a context for learning and examined how this context facilitated or inhibited supervision learning experiences for first-time supervisors. It draws on the qualitative findings of thirteen in-depth interviews whose data were analysed using the thematic analysis. This study found that the transitioning of first-time supervisors into the new role took place through their active participation in an organisational context. It concludes with the notion that workplace learning is a context-specific and interactive process. The social service organisation, with its unique features, serves the purpose of providing an environment for learning, with first-time supervisors afforded the opportunity to learn within the context and through interaction with other role-players. In summary, the study recommends a need for fostering of communities of practice, designing and management of workplace learning programmes, and ensuring the creation of sustainable and healthy workplaces. Keywords: social service organisation, organisational context, supervision practice, workplace learning, social service professions